Water frogs (Rana esculenta complex) in Serbia: Morphological data - Krizmanić I.I. (Archives of Biological Sciences, 2008)
The main purpose of this paper was to estimate morphometric variability of the water frog (Rana synklepton esculenta complex) population in Serbia. Altogether, 396 water frogs were collected at 15 localities in Serbia and analyzed using principal components for 18 selected indices, in addition to which correspondent analyses were conducted for 30 qualitative external morphological traits. The results showed that the population samples were heterogeneous and included three separate forms (Rana ridibunda, Rana lessonae and Rana kl. esculenta). Significant interspecific differences were found between R. ridibunda and R. lessonae, which are clearly distinct from each other. Rana kl. esculenta specimens were in an intermediate position between R. ridibunda and R. lessonae, with values more similar to the R. ridibunda parent species.